Pengaruh Latihan Plyometrik dan Kekuatan Otot Kaki terhadap Peningkatan Kecepatan Renang Gaya Dada Jarak 50 Meter Pada Siswa Ekstrakurikuler SMK Bina Bangsa Kersana, Kabupaten Brebes - M Fahri Dwi Prasetiyo; SUPRIYONO; Soedjatmiko; Hadi (Journal of Physical Education and Sports, 2026)
This study aimed to examine the effects of plyometric exercises, specifically jump to box and depth jump, and leg muscle strength on 50-metre breaststroke speed in students participating in extracurricular swimming at SMK Bina Bangsa Kersana, Brebes Regency. Using a quantitative experimental approach with a 2x2 factorial design, the study involved students undergoing plyometric training for four weeks, three sessions per week. The dependent variable was 50-metre breaststroke speed, and leg muscle strength was considered an attribute variable. The results indicated that both jump to box and depth jump exercises significantly increased swimming speed (F=215.207; p<0.05). Leg muscle strength also had a significant impact (F=51.909; p<0.05), with students possessing higher leg strength achieving faster swimming times. Furthermore, a significant interaction was observed between the type of plyometric exercise and leg muscle strength (F=8.206; p<0.05), suggesting that exercise effectiveness depends on the student’s leg strength. Overall, jump to box training was more effective than depth jump, and students with high leg strength showed the greatest improvement. These findings confirm that structured plyometric training, particularly jump to box exercises, combined with sufficient leg muscle strength, can optimize 50-metre breaststroke performance, making it a recommended approach for enhancing swimming speed in adolescent athletes.